IMPLEMENTASI KEBIJAKAN PENANGGULANGAN ANGKA STUNTING DI DESA BONGOIME KECAMATAN TILONGKABILA KABUPATEN BONE BOLANGO - Nusi, Rafliyanto Rafli; Tahir, Arifin Tahir Arifin; Nani, Yacob Nani Yacob (Jambura Journal of Administration and Public Service, 2025)
ABSTRACT The purpose of this study is to determine how the Implementation of the Stunting Rate Mitigation Policy in Bongoime Village, Tilongkabila District, Bone Bolango Regency, is seen from 3 important aspects, namely: (1) Policy Planning, namely related to the preparation of a stunting mitigation activity plan (2) Policy Implementation consisting of Human Development Cadre Development in stunting mitigation, stunting data management system in stunting mitigation, coordination in stunting mitigation, cooperation in stunting mitigation (3) Monitoring and evaluation in stunting mitigation. Through government policies and 8 convergence actions, researchers hope to be able to overcome stunting rates. This research method uses a descriptive approach with qualitative data analysis. The data collection techniques used are observation, interviews, and documentation. Based on the results of field research, the Implementation of the Policy for Accelerating the Reduction and Prevention of Stunting in Huangobotu Village, Kabila District, Bone Regency has not been implemented optimally according to the mandate stated in the Bone Bolango Regent Regulation number 105 of 2021. Judging from government policies and 8 convergence actions, namely the preparation of activity plans, coaching of human development cadres, stunting data management systems, coordination, cooperation, monitoring and evaluation. It can be concluded that the implementation of overcoming stunting rates in Bongoime Village, Tilongkabila District, Bone Bolango Regency has been implemented well by paying attention to regulations that have been implemented well and optimally. ABSTRAK Tujuan penelitian ini adakah untuk mengetahui bagaimana Implementasi Kebijakan Penanggulangan Angka Stunting di Desa Bongoime Kecamatan Tilongkabila Kabupaten Bone Bolango, dilihat dari 3 aspek penting yaitu: (1) Perencanaan Kebijakan yakni terkait penuyusunana rencana kegiatan penanggulangan stunting (2) Pelaksanaan Kebijakan yang terdiri dari Pembinaan Kader Pembangunan Manusia dalam penggulangan stunting, sistem manajemen data stunting dalam penanggulangan stunting, koordinasi dalam penanggulangan angka stunting, kerja sama dalam penanggulangan angka stunting (3) Monitoring dan evalusi dalam penanggulangan angka stunting. Melalui kebijakan pemerintah dan 8 aksi konvergensi peneliti berharap dapat meanggulangi angka stunting. Metode penelitian ini menggunakan pendekatan deskriptif dengan analisis data kualitatif. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dokumentasi. Berdasarkan hasil penelitian di lapangan bahwa Implementasi Kebijakan Percepatan Penurunan dan Pencegahan Stunting di Desa Huangobotu Kecamatan Kabila Bone Kabupaten belum terlaksana secara optimal sesuai amanah yang tertuang dalam Peraturan Bupati Bone Bolango nomor 105 tahun 2021. Dilihat dari kebijakan pemerintah dan 8 aksi konvergensi yaitu penyusunan rencana kegiatan, pembinaan kader pembangunan manusia, sistem manajemen data stunting, koordinasi, kerja sama, monitoring dan evaluasi. Dapat disimpulkan Implementasi penanggulangan angka stunting di Desa Bongoime Kecamatan Tilongkabila, Kabupaten Bone Bolango sudah terlaksana dengan baik dengan memeperhatikan peraturan yang sudah cukup dijalankan dengan baik dan optimal.